The effect of training status on inter-limb joint stiffness regulation during repeated maximal sprints - Clark, R. A. (Journal of Science and Medicine in Sport, 2009)
The purpose of this study was to examine the effect of anaerobic fatigue and training status on the joint stiffness (JS) regulation of the lower limbs. Twenty-two subjects participated in this study, with a group of athletes (ATH: n = 11, age: 22.1±9.9 yrs, ht: 181.9±6.3 cm, mass: 88.2±12.7 kg) compared to a group of non-athletes (NON: n = 11, age: 20.9±2.3 yrs, ht: 177.8±7.1 cm, mass: 80.9±22.0 kg). A modified phosphate decrement test, which consisted of eight 35m timed sprints separated by a 30 s active recovery, allowed for inducement of anaerobic fatigue while incorporating measures of sprinting performance and JS. Assessment of JS consisted of a single-legged 2.2 Hz spring-mass hopping protocol, measured for each limb. This test was performed prior to the warm-up and after sprints two, four and six. Data analysis consisted of repeated measures MANOVA comparing groups, limbs and test. Repeated measures ANOVAs were also performed on the sprint times and the magnitude of inter-limb JS difference. For all data analysis the alpha level was set at p < 0.05. Assessment of between limb JS revealed that the ATH group possessed significantly lower inter-limb variation in comparison with the NON group after completion of the first pair of sprints, potentially due to their training status offsetting some of the mechanical and neuromuscular effects of repeated stretch-shortening cycle (SSC) fatigue. This enhanced ability to regulate inter-limb JS, in addition to enhancing performance, may reduce the risk of injury by preserving mechanical efficiency and therefore reducing metabolic cost during SSC contractions.